ANALYSIS OF CLIMATE ANOMALY IMPACT OF LA-NINA 2010 ON EXPERIMENT FIELD SEMBAWA RESEARCH CENTER, SOUTH SUMATERA - Jamin Saputra (Widyariset, 2013)
La-Nina is an unusual climate changes that occurs in several years. The effect of climate anomaly on rubber plantation is very influential on rubber production. This research aims as analysis of La-Nina 2010 effects on experiment field Sembawa Research Centre. This research was carried out in experiment field Sembawa Research Centre at 2011. Research was conducted by analyzing the impact of rainfall in 2009 and 2010 on the availability of seed, reduction of tapping days, and rubber crop productivity. The results showed that the presence of La-Nina climate anomalies resulted in the availability of seed decreased by 50% for rootstock breeding. In addition, rubber production in the clones are susceptible to Colletotrichum leaf fall disease is reduced. Furthermore, tapping days were reduced 9 days because of the high intensity of rainfall. On the contrary, La-Nina caused a time delay of leaf fall sesion, so it did not give negative impact on productivity of Experiment Field Sembawa Research Centre. Attempts to reduce the impact of La-Nina climate anomalies have been done by planting specific location rubber clones, using rain guard technology, and giving extra fertilizer on the plants which are suffered by leaf fall disease.